ORIGIN AND PROPERTIES OF NATURALLY OCCURRING HAPTEN FROM ESCHERICHIA COLI - Anacker, R. L. (1964)
Anacker, R. L. (National Institute of Allergy and Infectious Diseases, Rocky Mountain Laboratory, Hamilton, Mont.), R. A. Finkelstein, W. T. Haskins, M. Landy, K. C. Milner, E. Ribi, and P. W. Stashak. Origin and properties of naturally occurring hapten from Escherichia coli. J. Bacteriol. 88:1705–1720. 1964.—Haptens found in preparations of endotoxin and in fractions of disrupted cells, particularly one termed “native hapten,” which appeared to be associated with the protoplasm of cells rather than with cell walls, have been further investigated with a view to establishing their origin and composition as well as their host-reactive properties. For this purpose, cells from a smooth strain of Escherichia coli O111:B4 were either extracted directly or disrupted and separated into cell-wall and protoplasmic fractions. Haptens were obtained by gel filtration of endotoxins, by trichloroacetic acid extraction of protoplasm, and by a mild acid hydrolysis of endotoxin. Several lines of evidence indicated that native hapten originated in the protoplasm rather than by autolysis or degradation of cell-wall endotoxin during procedures employed in disruption. In gel diffusion and quantitative precipitin tests, no hapten was identical with endotoxin, but native hapten was serologically the most complex of the haptens and precipitated the most antibody. Native and acid haptens, on a weight basis, fixed about 1% of the quantity of complement fixed by homologous endotoxin. Haptens did not stimulate the production of antibodies in mice or rabbits and did not elicit endotoxic host reactions. Chemically, native hapten differed from endotoxin and from acid hapten in that it lacked phosphorus, heptose, long-chain fatty acids, and 2-keto-3-deoxyoctonate. These substances did not appear to be determinants of antigenic specificity, but they may provide necessary bonds for assembling hapten-like units into fully antigenic and toxic macromolecules.